2007
DOI: 10.1002/ajmg.b.30578
|View full text |Cite
|
Sign up to set email alerts
|

No association between the DAT1 10‐repeat allele and ADHD in the Iranian population

Abstract: Association studies between attention-deficit hyperactivity disorder (ADHD) and the 10-repeat allele of a polymorphism (a 40 bp variable number of tandem repeats) in the dopamine transporter gene (DAT1) have resulted in mixed findings in different populations. We performed a case/control study to clarify the contribution of this allele with ADHD in the Iranian population. No association was observed between the 10-allele and disease (chi(2) = 0.081, P < 0.9). Furthermore, no significant difference was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For the 3ЈUTR VNTR, independent data were available from 15 TDT Brookes et al 2006b;Curran et al 2001b;Feng et al 2005b;Galili-Weisstub and Segman 2003;Hebebrand et al 2006;Kim et al 2005b;Kustanovich et al 2004;Lim et al 2006;Maher et al 2002;Mick et al unpublished data;Todd et al 2001a;Waldman et al 1998) and 19 Case-Control/HHRR studies (Bakker et al 2005;Banoei et al 2008;Bobb et al 2005;Carrasco et al 2004;Cheuk et al 2006b;Cook et al 1995;Cornish et al 2005;Das and Mukhopadhyay 2007;Genro et al 2007;Hawi et al 2003;Jiang et al 1999;Kim et al 2006b;Kopeckova et al 2008;Langley et al 2005;Qian et al 2004;Simsek et al 2005;Smith et al 2003;Swanson et al 2000b;Wang et al 2008), with the 480-bp (or 10-repeat) allele designated as the "risk" allele. Results of this meta-analysis, shown in Fig.…”
Section: Dopamine Transporter Gene (Dat1)mentioning
confidence: 99%
“…For the 3ЈUTR VNTR, independent data were available from 15 TDT Brookes et al 2006b;Curran et al 2001b;Feng et al 2005b;Galili-Weisstub and Segman 2003;Hebebrand et al 2006;Kim et al 2005b;Kustanovich et al 2004;Lim et al 2006;Maher et al 2002;Mick et al unpublished data;Todd et al 2001a;Waldman et al 1998) and 19 Case-Control/HHRR studies (Bakker et al 2005;Banoei et al 2008;Bobb et al 2005;Carrasco et al 2004;Cheuk et al 2006b;Cook et al 1995;Cornish et al 2005;Das and Mukhopadhyay 2007;Genro et al 2007;Hawi et al 2003;Jiang et al 1999;Kim et al 2006b;Kopeckova et al 2008;Langley et al 2005;Qian et al 2004;Simsek et al 2005;Smith et al 2003;Swanson et al 2000b;Wang et al 2008), with the 480-bp (or 10-repeat) allele designated as the "risk" allele. Results of this meta-analysis, shown in Fig.…”
Section: Dopamine Transporter Gene (Dat1)mentioning
confidence: 99%
“…Most association studies between DAT1 and ADHD have concentrated on a variable number of tandem repeat (VNTR) polymorphism in the 3'-untranslated region of the gene. Cook et al [ 7 ] first reported an association between the 10-reapeat allele of this polymorphism and ADHD, and several groups subsequently replicated this finding [ 8 - 13 ], although such replications are not ubiquitous and several studies have failed to detect any association [ 14 - 21 ]. More recent studies have examined additional markers across the DAT1 gene, finding stronger evidence for an association with multi-marker haplotypes containing the 10-repeat VNTR allele [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, 100 articles were read fully, and 34 articles were excluded because various reasons: e.g., missing data, overlapping samples in other publications or not fulfilling the inclusion criteria (Supplementary Table S4). Finally, 61 publications were included in the meta-analysis (Supplementary Table S5 including studies characteristics, demographics and quality assessment scores), including the current study results (Cook et al 1995; Waldman et al 1998; Jiang et al 1999; Lunetta et al 2000; Swanson et al 2000; Curran et al 2001; Todd et al 2001; Maher et al 2002; Smith et al 2003; Carrasco et al 2004; Kustanovich et al 2004; Galili-Weisstub et al 2005; Bakker et al 2005; Bobb et al 2005; Feng et al 2005; Kim et al 2005, 2006; Langley et al 2005; Simsek et al 2005; Hawi et al 2005, 2010; Brookes et al 2006; Cheuk et al 2006; Hebebrand et al 2006; Lim et al 2006; Asherson et al 2007; Brüggemann et al 2007; Qian et al 2007; Genro et al 2008; Johansson et al 2008; Wang et al 2008; Banoei et al 2008; Kopeckova et al 2008; Franke et al 2008, 2010; Niederhofer et al 2008; Kereszturi et al 2008; Gizer et al 2009; Wohl et al 2008; Martinez-Levy et al 2009, 2013; Dresler et al 2010; Aparecida da Silva et al 2011; Bidwell et al 2011; Das et al 2011; El-Tarras et al 2012; Hoogman et al 2013; de Azeredo et al 2014; Shang and Gau 2014; Hasler et al 2015; Sery et al 2015; Fonseca et al 2015; Agudelo et al 2015; Gomez-Sanchez et al 2016; Onnink et al 2016; Ortega-Rojas et al 2017; Stanley et al 2017; Wiguna et al 2017; Hong et al 2018; Morgan et al 2018). The summary of OR, SE, type of study (e.g., family TDT, case–control CC etc.…”
Section: Resultsmentioning
confidence: 99%